A comprehensive model for chemical bioavailability and toxicity of organic chemicals based on first principles - Forrest, Jay; Bazylewski, Paul; Bauer, Robert; Hong, Seongjin; Kim, Chang Yong; Giesy, John P.; Khim, Jong Seong; Chang, Gap Soo (Frontiers in Marine Science, 2014)
Here, we present a novel model to predict the toxicity and bioavailability of polychlorinated biphenyls (PCBs) as model compounds based on a first principles approach targeting basic electronic characteristics. The predictive model is based on an initio density functional theory. The model suggests HOMO-LUMO energy gap as the overarching indicator of PCBs toxicity, which was shown to be the primary factor predicting toxicity, but not the only factor. The model clearly explains why chlorination of both para positions is required for maximum toxic potency. To rank toxic potency, the "dipole moment" in relation to the most chemically active Cl-sites was critical. This finding was consistent with the accepted toxic equivalency factor (TEF) model for these molecules, and was also able to improve on ranking toxic potency of PCBs with similar TEFs. Predictions of HOMO-LUMO gap made with the model were consistent with measured values determined by synchrotron based X-ray spectroscopy for a subset of PCBs. HOMO-LUMO gap can also be used to predict bioaccumulation of PCBs. Overall, the new model provides an in silico method to screen a wide range of chemicals to predict their toxicity and bioavailability to act as an AhR agonist.